Collage Was Never Gone - Salado, Benjamín Romero (Hungarian Journal of English and American Studies, 2021)
Book review:Drąg, Wojciech. Collage in Twenty-First-Century Literature in English: Art of Crisis. New York and London: Routledge, 2019. 216 pages. ISBN 9780367437428. Hb. £120.00.